The first conspiracy : the secret plot to kill George Washington - Meltzer, Brad; Mensch, Josh (Flatiron Books, 2019)
"In 1776, an elite group of soldiers were handpicked to serve as George Washington's bodyguards. Washington trusted them; relied on them. But unbeknownst to Washington, some of them were part of a treasonous plan. In the months leading up to the Revolutionary War, these traitorous soldiers, along with the Governor of New York William Tryon and Mayor David Mathews, launched a deadly plot against the most important member of the military: George Washington himself. This is the story of the secret plot and how it was revealed. It is a story of leaders, liars, counterfeiters, and jailhouse confessors. It also shows just how hard the battle was for George Washington--and how close America was to losing the Revolutionary War. Taking place during the most critical period of our nation's birth, The First Conspiracy tells a remarkable and previously untold piece of American history that not only reveals George Washington's character, but also illuminates the origins of America's counterintelligence movement that led to the modern day CIA"--